HUBUNGAN KONSUMSI PURIN DENGAN HIPERURISEMIA PADA SUKU BALI DI DAERAH PARIW ISATA PEDESAAN - -, Hensen; Raka Putra, Tjokorda (journal of internal medicine, 2007)
Hyperuricemia is a condition of high consentration of uric acid in the blood. In most epidemiology study hyperuricemiais defined as level uric acid more than 7.0 mg/dl in men and more than 6.0 mg/dl in women. Hyperuricemia can be caused byseveral factors. Regarding the etiology hyperuricemia can be classified as primary, secondary and idiopathic hyperuricemia.Primary hyperuricemia related to genetic factor while secondary hyperuricemia caused by condition or other factors besidesgenetic factor such as high purin consumption, chronic kidney disease, certain drugs, alcohol and hypertension. To know theassociation between high purine diet and hyperuricemia, a cross sectional analytic study was conducted on Balinese in Ubudregion between Desember 2006 and January 2007. Sample study was Balinese age of 13 year old or above, agree to participateby informed consent. Descriptive statistic analysis on numeric data presented as mean mean ± SD, nominal and ordinal data inproportion. Inferential statistic analysis with bivariate simple logistic regression was performed and multiple logistic regressionwas used to know the independency of its association. Of 301 eligible samples, mean age was 40.85 ± 14.30 y.o, and 161 orang(53.5%) men and 139 (46.3%) women. Youngest age was 13 y.o and oldest was 85 y.o. Mean of purine consumption was 153.37± 77.83 mg/day and mean uric acid consentration was 5.14 ± 1.44 mg/dl with mean body mass index 22.57 ± 3.17 kg/m2.Prevalence of hyperuricemia on this study was 12%. High purine consumption was significantly associated with hyperuricemiaby analysis of prevalent ratio 22,82; CI 95% : 9.19 ? 56.66; p<0.001. On multivariate analysis with multiple logistic regressionhigh purin consumption also has independent association with hyperuricemia with prevalent ratio (PR) 57.30; IK 95% : 16.56 ?198.24; p < 0,001. Other factors that independently associated with hyperuricemia was obesity (PR : 7.21; IK 95% : 2.30 ? 22.60;p = 0.001), and chronic kidney disease stage 4 (PR : 74.73; IK 95% : 8.19 ? 681.60; p < 0.001). Age, alcohol consumption andchronic kidney disease stage 1 ? 3, hypertension not significantly associated with hyperuricemia in this population. Conclusion:high purine consumption was associated to hyperuricemia.